2010
DOI: 10.2215/cjn.06350909
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cystatin C and Acute Kidney Injury after Cardiopulmonary Bypass

Abstract: Background and objectives:Little is known about the performance of plasma cystatin C (CysC) in patients undergoing cardiopulmonary bypass (CPB) and its utility in the early diagnosis of acute kidney injury (AKI). In this post hoc analysis, the goal was to determine whether plasma cystatin C, measured 2 hours after the conclusion of CPB, is a reliable marker of AKI.Design, setting, participants, & measurements: Plasma CysC was measured in 150 patients undergoing CPB at the following times: preoperatively, 2 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 27 publications
5
33
0
Order By: Relevance
“…Cystatin C has shown great clinical potential as a biomarker of AKI in critically ill patients and cardiac surgery patients [17,18]. One recent study found that cystatin C was highly correlated with the development of AKI [19]. Similarly, in our present study, multivariate analysis results showed that elevated serum cystatin C levels were significantly correlated with the postoperative occurrence of AKI.…”
Section: Discussionsupporting
confidence: 83%
“…Cystatin C has shown great clinical potential as a biomarker of AKI in critically ill patients and cardiac surgery patients [17,18]. One recent study found that cystatin C was highly correlated with the development of AKI [19]. Similarly, in our present study, multivariate analysis results showed that elevated serum cystatin C levels were significantly correlated with the postoperative occurrence of AKI.…”
Section: Discussionsupporting
confidence: 83%
“…It is anticipated that these biomarkers will enable earlier diagnosis of AKI and facilitate prognostication [10-13, 17, 18]. Among these novel biomarkers, sCyC is considered the most promising functional marker for glomerular filtration [10, 17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Responding to the need for early and sensitive identification of patients with AKI, several biomarkers have been proposed over the past few years [10-13]. Perhaps most well-studied is cystatin C, a 13-kDa cysteine protease inhibitor that is produced by all nucleated cells at a constant rate and is renally cleared.…”
Section: Introductionmentioning
confidence: 99%
“…Three patients' required renal replacement therapy and 6 died in the hospital. Furthermore, they revealed that the serial measures of plasma CysC are highly correlated with the development of AKI (11) . Similarly, the other authors also found that serum Cys-C is a better marker of GFR than creatinine (12) , even in cases of sub-clinical renal dysfunction (13) .…”
Section: Discussionmentioning
confidence: 99%